2019
DOI: 10.4103/ajns.ajns_32_19
|View full text |Cite
|
Sign up to set email alerts
|

Results of a preventive rebleeding protocol in patients with ruptured cerebral aneurysm: A retrospective cohort study

Abstract: Objective: In 2015, a protocol to prevent rebleeding was implemented to improve the outcome of patients with ruptured intracranial aneurysm. We performed a single-center retrospective analysis to compare the outcomes of pre/post using protocol. Methodology: Over a 3-year period, 208 patients with ruptured cerebral aneurysm were treated at our institution. The protocol for preventing rebleeding was initiated in 2015. We compared the two cohorts between the group of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…362 With euvolemia as part of goal-directed therapy, DCI was observed in 13% of the patients in the goal-directed therapy group and in 32% of the patients in the control group (odds ratio, 0.324 [95% CI, 0.11–0.86]; P =0.021) in 1 study. 245 Duangthongphon and colleagues 320 found that initiation of the euvolemic protocol reduced DCI from 44.2% to 7.7% (odds ratio, 0.10 [95% CI, 0.04–0.23]; P <0.001). Furthermore, mortality rates in patients with a good WFNS grade decreased from 16.3% to 8.8% (hazard ratio, 0.80 [95% CI, 0.28–2.28]).…”
Section: 3 Management Of Cerebral Vasospasm and DCI After Asahmentioning
confidence: 99%
See 1 more Smart Citation
“…362 With euvolemia as part of goal-directed therapy, DCI was observed in 13% of the patients in the goal-directed therapy group and in 32% of the patients in the control group (odds ratio, 0.324 [95% CI, 0.11–0.86]; P =0.021) in 1 study. 245 Duangthongphon and colleagues 320 found that initiation of the euvolemic protocol reduced DCI from 44.2% to 7.7% (odds ratio, 0.10 [95% CI, 0.04–0.23]; P <0.001). Furthermore, mortality rates in patients with a good WFNS grade decreased from 16.3% to 8.8% (hazard ratio, 0.80 [95% CI, 0.28–2.28]).…”
Section: 3 Management Of Cerebral Vasospasm and DCI After Asahmentioning
confidence: 99%
“…In patients with aSAH, maintaining euvolemia can be beneficial in preventing DCI and improving functional outcomes. 320,321 2b B-NR 3. In patients with aSAH and symptomatic vasospasm, elevating systolic BP values may be reasonable to reduce the progression and severity of DCI.…”
mentioning
confidence: 99%
“…Even though those diagnostic tools are widely accepted, consensual treatments are very few 18 , 19 , and first consist in non-pharmacological approaches aiming at optimizing systemic and ergo cerebral hemodynamics, mainly through euvolemia 20 , 21 and elevated blood pressure 22 , 23 . The principal drug used in prophylaxis is nimodipine, which systemic administration has been shown to improve patients outcome 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective, single-center cohort study found a low incidence (3.1%) of rebleeding after the implementation of a strategy of intensive reduction of systolic blood pressure (target 120 ± 20 mm Hg) but did not include a control group [ 26 ]. Another retrospective, single-center study investigated the incidence of rebleeding before and after implementation of a blood pressure management protocol (systolic blood pressure target 160 mm Hg) [ 27 ]. After implementation of the protocol, a trend was observed toward a lower incidence of in-hospital rebleeding and a lower incidence of DCI compared with the time period prior to implementation of the protocol.…”
Section: Introductionmentioning
confidence: 99%